Inositol Phosphates and Synthesizing Enzymes: Implications in Neurodegenerative Disorders - Chisom J. Onu; Michael Adu; Mohamed Chakkour; Vikalp Kumar; Miriam L. Greenberg (Biomolecules)
Inositol is a vital sugar molecule involved in numerous signaling pathways required for cellular homeostasis and cell survival. Myo-inositol and its phospho-derivatives, inositol phosphates (IPs), are the most prevalent forms of inositol found in living cells. They are involved in regulating ion channels, metabolic flux, stress response, and other key biological processes. While emerging research has highlighted the significant roles of inositol phosphates in immunity, cancer, and metabolic diseases, there is a lack of comprehensive reviews on their roles in psychiatric and neurological disorders. This review aims to fill that gap by analyzing the existing literature on the importance of inositol phosphates in severe psychiatric and neurological conditions such as Parkinson’s disease, Alzheimer’s disease, bipolar disorder, amyotrophic lateral sclerosis, schizophrenia, and Huntington’s disease, underscoring the potential to pave the way for new treatment regimens for these debilitating disorders targeting inositol pathways.